Role of the Receptor Tyrosine Kinase Axl and its Targeting in Cancer Cells - Corno, Cristina; Gatti, Laura; Lanzi, Cinzia; Zaffaroni, Nadia; Colombo, Diego; Perego, Paola (Current Medicinal Chemistry, 2016)
Aberrant expression and activation of receptor tyrosine kinases (RTK) is a frequent feature of tumor cells that may underlie tumor aggressiveness. Among RTK, Axl, a member of the Tyro3-Axl-Mer family, represents a potential therapeutic target in different tumor types given its over-expression which leads to activation of oncogenic signaling promoting cell proliferation and survival, as well as migration and invasion. Axl can promote aggressiveness of various cell types through PI3K/Akt and/or MAPK/ERK, and its expression can be transcriptionally regulated by multiple factors. Deregulated Axl expression and activation have been shown to be implicated in reduced sensitivity of tumor cells to target-specific and conventional antitumor agents, but the precise mechanism underlying these phenomena are still poorly understood. Several small molecules acting as Axl inhibitors have been reported, and some of them are undergoing clinical investigation. In this review, we describe Axl biological functions, its expression in cancer and in drug-resistant tumor cells and the development of inhibitors tailored to this receptor tyrosine kinase.
Keywords: Cancer